PENGARUH EKSTRAK MENGKUDU (Morinda citrifolia) TERHADAP PENGOBATAN PENYAKIT PARASIT ARGULUS PADA IKAN KOMET (Carassius auratus) - Era Insivitawati; Tri Ari Setyastuti (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2020)
Disease is a threat that can be obstruct the fish growth. Argulus is one of the parasite that need to be watched out because it can interfere the fish growth, and cause secondary of infections that are dangerous for fish. The purpose of this study was to determine the benefits of noni for survival rate of fish and to determine the appropriate concentration of noni extract for culture the fish. This study uses a descriptive method to explain the results of the study. The results showed that giving noni extract at a dose of 1 drop / liter was able to make the argulus break away from fish and noni extract was effective in increasing fish immunity.